First record of Euzophera alpherakyella Ragonot, 1887 (Lepidoptera: Pyralidae: Phycitinae) from Uzbekistan - Shermatov, Malikjon R.; Mukhammedov, Muminjon M.; Kayumova, Oygulkhon I.; Botirov, Elyor A.; Mirzaeva, Gulnara S.; Kimyonazarov, Sardorbek Q. (Acta Biologica Sibirica, 2025)
This study presents the first confirmed record of Euzophera alpherakyella Ragonot, 1887 (Lepidoptera: Pyralidae: Phycitinae: Phycitini) from Uzbekistan. The species was identified based on two specimens collected from the Chimgan foothills in the southern part of the Fergana Valley. In addition to a detailed morphological description of adult moths, diagnostic images of the male and female genitalia are provided to support the identification of the species.